2003
DOI: 10.1021/bp025695h
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Sialylated N‐Linked Glycoprotein in Insect Cells: Role of Glycosidases and Effect of Harvest Time on Glycosylation

Abstract: Using a nonengineered Trichoplusia ni insect cell line, Tn-4s, infected with an Autographa californica recombinant baculovirus, 20% sialylation of human secreted placental alkaline phosphatase (SEAP) was observed. In contrast to this level of sialylation, intermediate complex forms with terminal galactose or N-acetylglucosamine were found in low proportions (<3% and <1%, respectively). We tested whether time of harvest or degradation of intermediate complex forms is responsible for this distribution of glycofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…Previous studies also reported supportive results: (i) sialylated N ‐glycans were detected on both native and recombinant proteins produced by insect cells (Davidson & Castellino 1991; Davis & Wood 1995; Ogonah et al. 1996; Joosten & Shuler 2003); (ii) significant activity of GlcNAcase was observed in insoluble fractions of lepidopteran cell homogenates (Kimura 1974, 1976; Altmann et al. 1993, 1995).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous studies also reported supportive results: (i) sialylated N ‐glycans were detected on both native and recombinant proteins produced by insect cells (Davidson & Castellino 1991; Davis & Wood 1995; Ogonah et al. 1996; Joosten & Shuler 2003); (ii) significant activity of GlcNAcase was observed in insoluble fractions of lepidopteran cell homogenates (Kimura 1974, 1976; Altmann et al. 1993, 1995).…”
Section: Introductionsupporting
confidence: 54%
“…Meanwhile, we previously reported that baculovirus-infected moth cells, Sf21AE (S. frugiperda origin) and TN5-5B1-4 (TN5; T. ni origin), synthesized N-glycans with sialic acid modification under b-D-N-acetylglucosaminidase (GlcNAcase)-inhibited conditions (Watanabe et al 2002). Previous studies also reported supportive results: (i) sialylated N-glycans were detected on both native and recombinant proteins produced by insect cells (Davidson & Castellino 1991;Davis & Wood 1995;Ogonah et al 1996;Joosten & Shuler 2003); (ii) significant activity of GlcNAcase was observed in insoluble fractions of lepidopteran cell homogenates (Kimura 1974(Kimura , 1976Altmann et al 1993Altmann et al , 1995. Despite of these findings, until recently, any GlcNAcase activity associated with the synthesis pathway of N-glycans was identified in the species.…”
Section: Introductionmentioning
confidence: 72%
“…We speculate that the cell death and lysis observed during the last 3 days of batch culture resulted in the release of glycan structures from the Golgi that had not completed the full biochemical synthesis necessary for formation of complex structures. The predominance of high mannose glycan structures has also been observed for cultures of insect cells (28)(29)(30) where the cells are known to undergo lytic cell death as a result of the baculovirus expression system.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, several studies had shown that T. ni cells could produce recombinant glycoproteins with terminally galactosylated N-glycans when infected with baculovirus expression vectors (32,35,38,39). Thus, it was theoretically possible to isolate a ␤4-galactosyltransferase family member from this organism.…”
Section: Figmentioning
confidence: 99%
“…However, more recent reports have shown that lepidopteran insect cell lines actually do have low levels of some of the glycosyltransferase activities mediating elongation of N-glycan termini, including N-acetylglucosaminyltransferase I (28,29), N-acetylglucosaminyltransferase II (28), ␤4-galactosyltransferase (30,31), and ␤4-N-acetylgalactosaminyltransferase (30). In addition, various reports have documented the presence of terminal N-acetylglucosamine, galactose, N-acetylgalactosamine, and even sialic acid residues on N-glycans produced by insect cells (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Finally, putative N-acetylglucosaminyltransferase, galactosyltransferase, and sialyltransferase genes have been identified in the D. melanogaster data bases (44), and the biochemical functions of the putative fly N-acetylglucosaminyltransferase I (45) and sialyltransferase (46) gene products have been experimentally confirmed in published studies.…”
mentioning
confidence: 99%